Italian ethnic community schools in Rio Grande do Sul: between the rural and urban milieu (1875 - 1914) - Terciane Ângela Luchese; Lúcio Kreutz; Eliana Gasparini Xerri (Universidade Estadual de Maringá, 2014)
Current paper is the partial result of a research, funded by CNPq, on the History of the Italian Ethnic Community Schools inBrazil (1875-1945). Investigating and mapping school organizations established by Italian immigrants in the state ofRio Grande doSul,Brazil, the text was built on Cultural History Studies and methodically processed by documental analysis, especially consular reports, documents of the Italian Ministry of Foreign Relations, newspapers, photographs and others. Several school initiatives may be found in different regions ofRio Grande do Sul, occupied by Italian immigrants or their descendants. Many were only temporary procedures and all were poorly systematized, albeit significant. They were different when installed in urban or rural areas. Moreover, they reveal the singularities and specific understanding of the importance of schooling. Since they were spaces for the constitution of Italian identity, Catholicity or even just for simply learning to read, write and calculate, it was an important educational space within the State´s scenario of the period.